Strategi Peningkatan Daya Saing pada UMKM Roti dan Kue di Kota Bandar Lampung - Febrian, Reyfido; Defrizal, Defrizal (Politeknik Negeri Medan, 2025)
The growth of the bakery industry has increased by 7-10% per year. The high demand for practical and affordable products has faced increasingly tight competition for UMKM Bread and Cake. This study analyzes strategies for increasing competitiveness with a qualitative approach through interviews with UMKM owners and co-founders. The results of the SWOT, IFE, and EFE analyses identified product quality, innovation, and social media as key factors of competitiveness, while dependence on fluctuating raw materials and suboptimal promotion are weaknesses of UMKM. The IFE score of 3.12 and EFE 3.36 indicate that the business strategy has been able to effectively recognize and utilize available external opportunities. Abstrak Pertumbuhan industri bakery meningkat mencapai 7-10% per tahun. Tingginya permintaan produk praktis dan terjangkau menghadapkan UMKM Roti dan Kue pada tantangan persaingan yang semakin ketat. Penelitian ini menganalisis strategi peningkatan daya saing dengan pendekatan kualitatif melalui wawancara pemilik dan co-founder UMKM. Hasil analisis SWOT, IFE, dan EFE mengidentifikasi kualitas produk, inovasi, serta media sosial sebagai faktor kunci daya saing, sementara ketergantungan pada bahan baku bersifat fluktuatif dan promosi yang belum optimal menjadi kelemahan UMKM. Skor IFE 3,12 dan EFE 3,36 menunjukkan bahwa strategi usaha telah mampu secara efektif mengenali serta memanfaatkan peluang eksternal yang tersedia.